Analysis of the application of «My therapy application» to the compliance of drinking (ARV) in HIV/AIDS people in Kompeda, Surabaya - Devy Vatma Rositasari; Erika Martining Wardani; Riska Rohmawati; Nur Hidaayah (Журнал инфектологии)
HIV/AIDS sufferers are required to take antiretrovirals (ARVs), on time and with discipline, but many sufferers will forget to take their medication. In overcoming this problem by providing the my therapy application. The aim of this study was to analyze the effect of applying the my therapy application on adherence to taking ARV medication in HIV/ AIDS people at Kompeda Surabaya.The research design used the Pre-Experiment, with the one group pre-test and post-test design approaches. The study population consisted of 74 people with a sample size of 62 respondents using probability sampling technique. The variables of this study are the application of digital my therapy and adherence to taking ARV medication. Data analysis used the Wilocoxon Signed Rank Test.The results of this study were obtained after being given the application of the my therapy application to people with HIV/AIDS with the results of the statistical wilocoxon test obtained a p-value of 0.000, it can be concluded that H1 is accepted meaning that there is an effect of the application of my therapy on adherence to taking ARV medication in people with HIV/AIDS at Kompeda Surabaya.The conclusion in this study was that before the intervention was given, most patients did not adhere to taking medication. Therefore, it is hoped that HIV/AIDS patients can maintain adherence to taking ARV medication, so that it can inhibit the growth of the HIV/AIDS virus. It is hoped that Komeda Surabaya will be able to overcome the importance of special treatment with education for adherence to taking ARV medication for people with HIV/AIDS at Kompeda Surabaya.